Study of the Weeb Simp Phenomenon in VTuber Using the Uses and Gratifications Theory: Studi Fenomena Weeb Simp pada VTuber dengan Teori Uses and Gratifications - Maulana, Muhammad Rizky; Dharma, Ferry Adhi (House of Wisdom: Journal on Library and Information Sciences, 2025)
General Background: The rise of virtual YouTubers (VTubers) represents a significant development in digital entertainment, creating a new space for audience interaction and community formation. Specific Background: The phenomenon of "simping" within the weeb subculture toward VTubers is a notable aspect of this new media landscape. Knowledge Gap: Existing research has yet to fully explore the specific psychological and emotional gratifications that drive this particular fan behavior. Aims: This qualitative study aims to understand how active members of the VTuber fan community utilize and find gratification in their interactions with virtual idols. Results: Findings from interviews with nine informants revealed four key motivations: diversion from real-life stress, cultivation of parasocial relationships, strengthening of social identity within the community, and information seeking (surveillance). Novelty: This research provides a unique and in-depth analysis of the "weeb simp" phenomenon, illuminating the complex ways in which VTubers function as more than just entertainers. Implications: The study concludes that VTubers serve as crucial social agents, fulfilling significant psychological and emotional needs for their audience. Highlights : The study analyzes how VTuber fans, or "weeb simps," fulfill their needs through interaction with virtual idols. The findings identify four key motivations for fan engagement: diversion, personal relationships, social identity, and surveillance. The research concludes that VTubers act as social agents, fulfilling psychological and emotional needs for their audience. Keywords : VTuber, Uses and Gratifications, Parasocial Relationships, Fan Communities, Audience Motivation